Identification of ethnomedicinally important Kaempferia L. (Zingiberaceae) species based on morphological traits and suitable DNA region - Labrooy, Catherine Dharshini; Abdullah, Thohirah Lee; Stanslas, Johnson (Elsevier, 2018)
Nuclear ribosomal internal transcribed spacer (ITS) sequences and morphological characteristics were used to identify medicinally important Kaempferia species cultivated in Peninsular Malaysia. Six species were evaluated for parameters such as nucleotide diversity (0.458) and estimated values of transition/transversion bias (0.89) using sequence data. Maximum parsimony (MP) analysis inferred divergence pattern in the Kaempferia genus. The resulting phylogenetic tree was compared to one formed using morphological traits. Morphological and molecular data both show 3 distinctive groupings within selected Kaempferia species. ITS 4 and 5 sequences are proposed as DNA barcodes for identification of Kaempferia species. In terms of morphological traits, plant habit, rhizome colour and leaf variation can be used for preliminary identification of this genus.